Transverse momentum spectra and nuclear modification factors of charged particles in Xe-Xe collisions at √sNN=5.44 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Köhler, Markus Konrad; Klewin, Sebastian; Leardini, Lucia; Mercado Pérez, Jorge; et al. (Physics letters, 2019)
Transverse momentum (pT ) spectra of charged particles at mid-pseudorapidity in Xe-Xe collisions at sNN=5.44TeV measured with the ALICE apparatus at the Large Hadron Collider are reported. The kinematic range 0.15<pT<50GeV/c and |η|<0.8 is covered. Results are presented in nine classes of collision centrality in the 0-80% range. For comparison, a pp reference at the collision energy of s=5.44 TeV is obtained by interpolating between existing pp measurements at s=5.02 and 7 TeV. The nuclear modification factors in central Xe-Xe collisions and Pb-Pb collisions at a similar center-of-mass energy of sNN=5.02 TeV, and in addition at 2.76 TeV, at analogous ranges of charged particle multiplicity density 〈dNch/dη〉 show a remarkable similarity at pT>10 GeV/c. The centrality dependence of the ratio of the average transverse momentum 〈pT〉 in Xe-Xe collisions over Pb-Pb collision at s=5.02 TeV is compared to hydrodynamical model calculations.